Macroscopic and microscopic approaches for identification of fungi from plant soil of Cameron Highlands - Salvamani, Shamala; Mohammad Nawawi, Norazah (Hibiscus Publisher, 2014)
There were seven cultures of fungi isolated from vegetable soil in Cameroon Highlands. In this research project, two techniques have been used for the identification purpose, which are macroscopic and microscopic morphology approaches to identify the genus of the fungus. Macroscopic identification based on the characteristic of the fungus grown on the PDA plate and the microscopic identification was based on the spore and hyphae using lactophenol blue dye. Four genus that have been successfully identified using this approach are Aspergillus, Fusarium, Rhizopus and Gliocladium.